Four Christmases [videorecording (DVD)] - Favreau, Jon; Steenburgen, Mary; Duvall, Robert; Vaughn, Vince; Yoakam, Dwight; Chenoweth, Kristin; Witherspoon, Reese, 1976-; Spacek, Sissy; Gordon, Seth (New Line Cinema, 2009)
When happily unmarried San Francisco couple Kate and Brad find themselves socked in by fog on Christmas morning, their exotic vacation plans morph into the family-centric holiday they had, until now, gleefully avoided. Out of obligation, and unable to escape, they trudge to not one, not two, but four relative-choked festivities.